2006
DOI: 10.1016/j.pain.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Catechol- O -methyltransferase gene polymorphisms are associated with multiple pain-evoking stimuli

Abstract: Variations in the gene encoding catechol-O-methyltransferase (COMT) are linked to individual differences in pain sensitivity. A single nucleotide polymorphism (SNP) in codon 158 (val(158)met), which affects COMT protein stability, has been associated with the human experience of pain. We recently demonstrated that three common COMT haplotypes, which affect the efficiency of COMT translation, are strongly associated with a global measure of pain sensitivity derived from individuals' responses to noxious thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
4
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(270 citation statements)
references
References 21 publications
12
249
4
5
Order By: Relevance
“…Therefore, it can be considered a somewhat novel finding that pain catastrophizing had a positive association with pain intensity in this cohort of patients seeking operative treatment of their shoulder pain. We selected the COMT gene because of its high priority candidate rating (Belfer et al, 2004) and its previous influence on pain perception for healthy subjects (Zubieta et al, 2003;Diatchenko et al, 2005Diatchenko et al, , 2006. The influence of COMT genotype for clinically relevant phenotypes has been questioned in the literature (Kim et al, 2006), but our data suggested that COMT diplotype had an influence on pain ratings, at least when determined by LPS and APS/HPS groups.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, it can be considered a somewhat novel finding that pain catastrophizing had a positive association with pain intensity in this cohort of patients seeking operative treatment of their shoulder pain. We selected the COMT gene because of its high priority candidate rating (Belfer et al, 2004) and its previous influence on pain perception for healthy subjects (Zubieta et al, 2003;Diatchenko et al, 2005Diatchenko et al, , 2006. The influence of COMT genotype for clinically relevant phenotypes has been questioned in the literature (Kim et al, 2006), but our data suggested that COMT diplotype had an influence on pain ratings, at least when determined by LPS and APS/HPS groups.…”
Section: Discussionmentioning
confidence: 80%
“…The focus of the genetic analysis was on the COMT gene because it is a commonly investigated pain candidate gene, with recent studies suggesting a meaningful influence on human pain perception (Zubieta et al, 2003;Diatchenko et al, 2005Diatchenko et al, , 2006. Furthermore, its role in modulating nociceptive input was theoretically complementary to the psychological factors we were studying.…”
Section: Genetic Samples-subjectmentioning
confidence: 99%
“…Indeed, similar disparate results in human genetic studies of pain sensitivity have been shown to occur with the common polymorphism of the catechol-Omethyltransferase gene (Val158Met) [34]; while one study found a significant genetic association [49], another did not [24], a third described a significant effect but not for that polymorphism [16], and a fourth reported that findings depended on stimulus modality [15].…”
Section: Discussionmentioning
confidence: 93%
“…No medication was injected through the epidural catheter for at least 20 min after the intrathecal injection. Women were asked to rate their pain according to an 11-point verbal rating score (VRS) for pain intensity in which 0 represented no pain and 10 the worst pain imaginable before CSE and at 5,10,15,20,30,45 and 60 min after spinal injection. Maternal blood pressure and fetal heart rate were also recorded at the same time points.…”
Section: General Clinical Methodsmentioning
confidence: 99%
“…Based on SNPs rs6269, rs4633, rs4818, and rs4680, 3 functional haplotypes have been defined, namely low pain sensitivity (GCGG), average pain sensitivity (ATCA), and high pain sensitivity (ACCG) (65 ). More recently, the low pain sensitivity haplotype has been associated with the highest pain score and opioid consumption in the postoperative pain setting (60 ).…”
Section: Comtmentioning
confidence: 99%